Nowe materiały tzw. fazy wczesnopucharowej osadnictwa protoneolitycznego na Pomorzu - Galiński, Tadeusz (Folia Praehistorica Posnaniensia, 2018)
The article presents stone and pottery materials from Tanowo, site 3, near Szczecin, excavated in the years 1999-2002 (trench II). The materials represent the late phase o f proto-Neolithic occupation dated back to 3300-2900/2800 BC. An animal bone sample from settlement pit in trench II is dated back to 5170 +/- BP (Poz - 1385).